Can we translate sounds into words? A response to Leo Groarke`'s "Auditory Arguments: The Logic of ‘Sound’ Arguments": A response to Leo Groarke`s: Auditory Arguments: The Logic of ‘Sound’ Arguments - Kisicek, Gabrijela (Informal Logic)

(untitled) (Informal Logic, 2018)
This comment to Leo Groarke`'s "Auditory Arguments: The Logic of ‘Sound’ Arguments" is a contribution to the better understanding of an auditory argument as a part of analysis of an argumentative discourse. The emphasis is on human sound i.e. prosodic features of spoken language and its argumentative function. Paper presents sort of “auditory dictionary” which might be of use in sound analysis. It also gives one possible solution of translating sound into words by using visual images as mediators.